2017
DOI: 10.3892/br.2017.910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dark-colored maple syrup on cell proliferation of human gastrointestinal cancer cell

Abstract: Maple syrup is a natural sweetener that is commonly consumed worldwide. While maple syrup mainly comprises sucrose, it also contains phytochemicals that present various biological effects. Maple syrup is made by boiling down sap, and its color and composition vary in accordance with the sap collection season. Typically, seasonal progression is associated with darker syrup color, and antioxidant activity is proportional to the increasingly dark color. The authors previously reported that maple syrup demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…In our previous study of the anticancer effects of different grades of maple syrup, it was reported that dark-colored maple syrup reduced AKT, also termed protein kinase B, activation, and therefore significantly inhibited proliferation and invasion in CRC cells (30). In addition, another previous study showed that it significantly inhibited growth in other types of gastrointestinal cancer cell (31). This suggests that dark-colored maple syrup may be a useful dietary factor for potentially preventing cancer progression.…”
Section: Introductionmentioning
confidence: 95%
“…In our previous study of the anticancer effects of different grades of maple syrup, it was reported that dark-colored maple syrup reduced AKT, also termed protein kinase B, activation, and therefore significantly inhibited proliferation and invasion in CRC cells (30). In addition, another previous study showed that it significantly inhibited growth in other types of gastrointestinal cancer cell (31). This suggests that dark-colored maple syrup may be a useful dietary factor for potentially preventing cancer progression.…”
Section: Introductionmentioning
confidence: 95%
“…Maple syrup is a popular natural sweetener that is consumed worldwide. Although sucrose constitutes ~60% of maple syrup, it also contains smaller concentrations of glucose and fructose [4,5,6,7,8]. However, Taga et al has shown that maple syrup contains rare reducing carbohydrates such as xylose, arabinose, ribose, and mannose, using capillary electrophoresis (CE) analysis of 1-phenyl-3-methyl-5-pyrazolone (PMP) derivatives [9].…”
Section: Introductionmentioning
confidence: 99%
“…As the season progresses, maple syrup’s color darkens, and it is classified into four grades: golden, amber, dark, and very dark [ 1 ]. Maple syrup has various biological effects, and it has also been reported that different grades of maple syrup could have different biological effects [ 2 , 3 , 4 , 5 , 6 ]. Although maple syrup has a low glycemic index (GI), it is mostly sucrose with a small amount of glucose and fructose [ 5 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maple syrup has various biological effects, and it has also been reported that different grades of maple syrup could have different biological effects [ 2 , 3 , 4 , 5 , 6 ]. Although maple syrup has a low glycemic index (GI), it is mostly sucrose with a small amount of glucose and fructose [ 5 , 7 , 8 , 9 ]. It was reported that maple syrup contains pentoses, such as xylose, arabinose, and ribose, and polysaccharides, such as inulin [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%